icio : Economic Analysis with Inter-Country Input-Output Tables in Stata - Belotti, Federico (World Bank, Washington, DC, 2020)
Several new statistical tools and analytical frameworks have been developed recently to measure countries' and sectors' involvement in global value chains. Such wealth of methodologies reflects that different empirical questions call for distinct accounting methods, along with different levels of aggregation of trade flows. This paper is a companion to the conceptual framework presented in Borin and Mancini (2019). The paper describes a new Stata module, icio, that allows the user to construct the most appropriate measure for given empirical questions on trade in value-added and participation in global value chains of countries and sectors. By exploiting inter-country input-output tables, icio provides decompositions of aggregate, bilateral, and sectoral exports and imports according to the source and destination of their value-added content. As different measures are suited to address distinct economic questions, icio is designed to be flexible also in this respect.